2015
DOI: 10.4103/2229-3485.148816
|View full text |Cite
|
Sign up to set email alerts
|

A questionnaire study on the knowledge, attitude, and the practice of pharmacovigilance among the healthcare professionals in a teaching hospital in South India

Abstract: Objective:The primary objective of this study was to evaluate the knowledge, attitude, and practices (KAP) of the healthcare professionals about pharmacovigilance in Dhanalakshmi Srinivasan Medical College and Hospital (DSMCH), Perambalur (Tamil Nadu), a tertiary care teaching hospital. The second primary objective was to assess the causation of underreporting of adverse drug reactions (ADRs) as it needs to be well-assessed in India. The secondary objective was to compare the findings of this study with the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
125
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(159 citation statements)
references
References 15 publications
29
125
5
Order By: Relevance
“…These findings are in correlation with findings of a study conducted by Gupta SK, et al 12 Majority 65.45% doctors knew the existence of NPP. Also, that is, 79.59% doctors knew that in India the CDSCO is a regulatory body responsible for monitoring ADRs.…”
Section: 14supporting
confidence: 81%
See 1 more Smart Citation
“…These findings are in correlation with findings of a study conducted by Gupta SK, et al 12 Majority 65.45% doctors knew the existence of NPP. Also, that is, 79.59% doctors knew that in India the CDSCO is a regulatory body responsible for monitoring ADRs.…”
Section: 14supporting
confidence: 81%
“…These questions were designed based on earlier studies for assessing KAP of ADR reporting. [10][11][12] The questionnaire had 22 questions in all. Respondents were not required to mention their identity on the questionnaires.…”
Section: Study Populationmentioning
confidence: 99%
“…These findings were in accordance with findings of a study conducted by Gupta et al 15 Only 37.89% healthcare professionals knew the existence of PvPI. Whereas only few, i.e., 43.73% health-care professionals knew that in India the CDSCO is a regulatory body responsible for monitoring ADRs.…”
Section: Discussionsupporting
confidence: 83%
“…[14][15][16] But the ground reality is, in India, ADR reporting by physician accounted to 64.4%. 17 However, survey in Saudi Arabia showed that 49.3% of the physicians suggested that only serious ADRs should be reported.…”
Section: Discussionmentioning
confidence: 99%